Analisis Faktor Produksi Usahatani Di Kabupaten Enrekang Sulawesi Selatan - Niar, Hikma; Irmawati (Jurnal Online Manajemen ELPEI, 2025)
This study, entitled "Analysis of Farming Production Factors in Enrekang Regency, South Sulawesi," was conducted in Banti Village, Baraka District, Enrekang Regency. The aim was to determine the significant influence of production factors such as land area, seeds, labor, fertilizer, and pesticides on shallot production in Banti Village, Baraka District, Enrekang Regency. The results showed that land area, seeds, and fertilizer had a positive but insignificant effect on production volume. The results showed that labor and specifications had a negative and insignificant effect on production, but still helped improve the standard of living of farmers. Keywords: Land, seeds, labor, fertilizer, and pesticides.